The effect of structural change on the digestibility of sarcoplasmic proteins in Nanjing dry-cured duck during processing. (20th July 2018) - Du, X J; Sun, Y Y; Pan, D D; Wang, Y; Ou, C R; Cao, J X
ABSTRACT: To evaluate the effect of structural change on the digestibility of sarcoplasmic proteins in Nanjing dry-cured duck during processing, carbonyl content, sulfhydryl (SH ) group, disulfide (S-S ) group, surface hydrophobicity, particle size, secondary structures, and in vitro digestibility were determined. During processing, carbonyl content increased; SH groups turned into S-S groups; α-helix turned into β-sheet. From marinating to early dry-ripening stage, surface hydrophobicity increased but particle size decreased, whereas these had opposite tendencies at the late dry-ripening stage. The in vitro digestibility of pepsin decreased at drying-curing and drying-ripening stages, whereas the one of pancreatic proteases kept stable until late drying-ripening stage. We concluded that salting, drying, and protein oxidation caused the denaturation and aggregation during processing. The oxidation and aggregation of sarcoplasmic proteins of Nanjing dry-cured duck resulted in a loss of nutritional quality during drying-ripening stage.